One health: a long road ahead - Singh, Srishti; Jha, S. K. (International Journal Of Community Medicine And Public Health, 2023)
One health (OH) is a collaborative, multisectoral, coordinated and transdisciplinary approach-working at the local, regional, national, and global levels – with the goal of achieving optimal health outcomes by recognizing the interconnection between people, animals, plants, and their shared environment. OH framework was officially recommended as an approach to deal with zoonotic infectious diseases by the world health organization in 2008 of which the core components of the framework are food safety, zoonoses and antibiotic resistance. India has taken some steps towards the OH concept by promoting collaboration among various sectors and allocating the required resources. However, still a lot needs to be done to overcome the challenges. Implementing systematic zoonotic surveillance; regulated antibiotic use among humans and animals; development of a zoonotic registry in the country; constitution of a wide network of academic, research, pharmaceutical and various implementation stakeholders from different sectors is the need of the hour to effectively use OH. Implementing a ’ OH ’ system consists of emphasizing the intersections of humans, domestic and wild animal populations as well as plants and ecosystems. By promoting collaboration across all sectors, a OH approach can achieve the best health outcomes for people, animals, and plants in a shared environment.